2019
DOI: 10.1111/ggi.13725
|View full text |Cite
|
Sign up to set email alerts
|

Factors of post‐stroke dementia: A nationwide cohort study in Taiwan

Abstract: Aim We investigated the long‐term risk of dementia for up to 10 years in patients with stroke and broadened the correlates. Methods We carried out a case–control study using the Taiwan National Health Insurance Research database in 2000 with a sampled population of 1 million. The study cohort comprised 8236 patients with stroke and no dementia history. We carried out a 1:1 case–control matched analysis on estimated propensity scores. Cox proportional hazards regressions were carried out to estimate the risk of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 30 publications
2
17
0
Order By: Relevance
“…We demonstrated that patients with stroke had signi cantly higher incidence of dementia rates within 3year follow-up, and the incidence of dementia in male patients with stroke was higher than that of female patients with stroke. A pooled analysis of international data classi ed important contributors and risk factors to post-stroke dementia, and age over 65 and female gender are the mentioned risk factors [26,27]. The mean age in our study and the result that stroke patients had higher incidence of dementia match with this analysis, however the effect of gender did not.…”
Section: Discussionsupporting
confidence: 68%
“…We demonstrated that patients with stroke had signi cantly higher incidence of dementia rates within 3year follow-up, and the incidence of dementia in male patients with stroke was higher than that of female patients with stroke. A pooled analysis of international data classi ed important contributors and risk factors to post-stroke dementia, and age over 65 and female gender are the mentioned risk factors [26,27]. The mean age in our study and the result that stroke patients had higher incidence of dementia match with this analysis, however the effect of gender did not.…”
Section: Discussionsupporting
confidence: 68%
“…The Mini-Mental State Examination (MMSE) is a widely used tool to identify and rank cognitive impairment in elders [18]. It consists of a group of questions covering seven groups of cognitive functions, (1) orientation to time, (2) orientation to place, (3) registration of three words, (4) attention and calculation, (5) recall of three words, and (6) language and visual construction, with the maximum score of 30 points [19]. MMSE is found to be insensitive to the early signs of dementia, especially in highly educated individuals [20], so it is not considered in this study.…”
Section: Measurementsmentioning
confidence: 99%
“…Various risk factors make individuals prone to dementia. According to a nationwide cohort study in Taiwan, it is found that people with the disease of ischemic stroke, transient ischemic attack and cerebrovascular hemorrhage had a significantly greater risk of dementia afterward [5]. Community studies show that people with a lack of education or low education are more likely to have dementia or Alzheimer's disease [6].…”
Section: Introductionmentioning
confidence: 99%
“…With TLD, researchers have identified several significant associations with high clinical impact, such as the association between nucleoside analogs and the risk of post liver resection hepatocellular carcinoma recurrence, and risk factors for poststroke dementia [41][42][43]. The thesis of the AOP model is that prescriptions solely comprising common D-M combinations in a large database, such as TLD, have a higher possibility of being substantiated.…”
Section: Principal Findingsmentioning
confidence: 99%